Retraction Notice: Quay crane assignment in container terminals using a genetic algorithm - Sanaa, Aidi; Imane, Torbi; Mohamed, Mazouzi (Computer Science and Information Technologies, 2025)
Notice of Retraction: A. Sanaa, T. Imane, and M. Mohamed, "Quay crane assignment in container terminals using a genetic algorithm," Computer Science and Information Technologies, vol. 6, no. 1, 2023, pp. 40-47, doi: 10.11591/csit.v6i1.p40-47." This article has been determined to have contravened IAES publication principles following a thorough and thoughtful review of its content by a duly established expert committee, following the report of Hizia Amani and Rachid Chaib. In particular, the content of the following source was copied without proper attribution in this article: H. Amani, L. Bouyaya, R. Chaib, F. Z. Djekrif, and M. Aizi, "Optimization of Quay Crane Scheduling Problem at the Port of Algeria," in I. Kabashkin, I. Yatskiv, and O. Prentkovskis, Eds. Cham: Springer International Publishing, 2023, pp. 232–241, doi: 10.1007/978-3-031-26655-3_21. Consequently, IAES has removed the content of this article from this online system. The authors concurred with the decision to retract when it was communicated. Additionally, the authors requested that the article be removed.The article is not suitable for research or citation. We apologize for any inconvenience this may have caused.